Optimizing CDN Modeling with API Integration Using Time To- Live (TTL) Caching Technique - Hendri, Hendri; Rukmi Sari Hartati; Linawati Linawati; Dewa Made Wiharta (Dinasti Review, 2024)
This research examines the implementation of Time-To-Live (TTL) caching within a Content Delivery Network (CDN) model that incorporates API integration, structured to simulate a hierarchical configuration of CDN edge servers across Indonesia's administrative tiers. The analysis centers on the influence of TTL configurations on critical performance metrics—namely latency, cache hit ratio, throughput, and bandwidth consumption. Special focus is placed on scenarios in which a 1 MB data object originating from the Central Government (Level 1) is primarily accessed through edge servers positioned at the village level (Level 5). The simulation envisions a CDN architecture where in the Central Government functions as the Main Server/Origin Server, with edge servers extending across 38 provinces (Level 2), 514 regencies (Level 3), 7,277 districts (Level 4), and 83,763 villages (Level 5).